The performance of NLST screening criteria in Asian lung cancer patients. Issue 1 (December 2015) - Kumar, Vivek; Becker, Kevin; Zheng, Huo; Huang, Yiwu; Xu, Yiqing
Abstract Background Screening high-risk individuals with low dose CT decreased lung cancer mortality in the National Lung Screening Trial (NLST), but the validity of directly extrapolating these results to an Asian population is unclear. Using statistical models on Surveillance, Epidemiology and End Result (SEER) data, 27 % of lung cancer patients in the United States were estimated to meet the screening criteria. This study aims to evaluate the performance of the NLST criteria in Asian lung cancer patients and to examine the characteristics of those who did not meet the criteria. Methods We conducted a retrospective study of Asian lung cancer patients treated at Maimonides Cancer Center between 1/2008 and 6/2013. Data on demographics, smoking history, cancer stage, histology, and EGFR/ALK mutation status were collected and analyzed. Results Of 116 eligible patients, 75 patients (65 %) were smokers which included 26 light smokers (22 %). Thirty-two patients (27.8 %) met the NLST criteria. Extending the age limit to 79 would cover 8 % more patients while removing the lower age limit would only cover 2 % more. None of the female patients met the criteria as they were all never or light smokers. Two-thirds of male patients younger than age 55 were never or light smokers. The EGFR mutation rate was 67 % in female and 28 % in male patients. Conclusion The percentage of Asian patients meeting the NLST criteria is similar to that estimated for the United States population, suggesting that extension of the criteria to an Asian population is valid. One-third of the patients were non-smokers and an additional one-fourth were light smokers, comprised mostly of female and young male patients. Further strategies for screening these individuals based on non-tobacco factors are urgently needed.